Size optimization methods to approximate equivalent mechanical behaviour in thermoplastics. Issue 1 (12th October 2020) - Althammer, Florian; Ruf, Florian; Middendorf, Peter
Abstract: This paper investigates the possibility of producing an equivalent structural behaviour of two components each consisting of a different material. This is achieved through the implementation of structural optimizations. It is assumed that the initial structure is produced by conventional injection moulding and the structure to be optimized is 3D printed. For comparison, two material pairings currently used in both processes are considered. As a structural optimization method, thickness optimizations are performed in order to change the resulting cross-section of the prototype. At the beginning, the mechanical problem is formulated analytically and methods for structural optimization are evaluated. With finite element analysis, two methods are presented, which introduce the generation of a variable thickness distribution in rib structures. The first method represents a state-of-the art optimization. Ribs are directly optimized by approximating cross-section forces and moments of the prototype rib and the initial rib. The second method represents a new approach to the optimization of thin-walled structures. Local stress distributions and resulting triaxiality states, which are approximated in an intermediate step, are analysed. A newly developed finite element structure is presented, with which it is possible to generate discrete triaxiality fields and determine the necessary local thickening. This method can be used in order to produce functional prototypes in early design stage. The substituted plastic parts are usually produced by injection moulding, which initially requires a high expenditure of time and money for tool construction. Additive manufacturing represents a solution here to accelerate the development process. However, these 3D-printed prototypes are, regarding the material properties and resulting mechanical behaviour, different to the injection-moulded ones. Graphical Abstract: